2018
DOI: 10.1007/s00345-018-2288-5
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary renal cell carcinoma syndromes: diagnosis, surveillance and management

Abstract: Increasing knowledge of the natural history and genetic basis has led to characterisation and tailored management of hereditary RCC syndromes. International data sharing of inherited RCC gene variant information may enable evidence-based improvements in the diagnosis, surveillance protocols and management of these rare conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
110
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(117 citation statements)
references
References 53 publications
2
110
0
5
Order By: Relevance
“…In 90% of cases, these tumours exhibit alterations in the von Hippel–Lindau tumour suppressor (VHL) gene on chromosome 3 [25]. Most tumours are sporadic, but multiple bilateral tumours are seen in von Hippel–Lindau syndrome, a rare autosomal dominant condition also associated with a variety of other tumours that include haemangioblastomas of the retina and central nervous system [26]. Multifocal sporadic tumours are rare and a recent study has shown that apparent multifocality may be due to retrograde venous invasion from a single tumour [27].…”
Section: Resultsmentioning
confidence: 99%
“…In 90% of cases, these tumours exhibit alterations in the von Hippel–Lindau tumour suppressor (VHL) gene on chromosome 3 [25]. Most tumours are sporadic, but multiple bilateral tumours are seen in von Hippel–Lindau syndrome, a rare autosomal dominant condition also associated with a variety of other tumours that include haemangioblastomas of the retina and central nervous system [26]. Multifocal sporadic tumours are rare and a recent study has shown that apparent multifocality may be due to retrograde venous invasion from a single tumour [27].…”
Section: Resultsmentioning
confidence: 99%
“…Genetic risk factors are known to play a role in sporadic RCC development [7, 8]. Patients who have at least one first degree relative with RCC are at an increased risk of developing the disease (OR 1.4, 95% CI 0.71–2.76) [9].…”
Section: Resultsmentioning
confidence: 99%
“…Signature 2, associated with APOBEC family of cytidine deaminases is the next most common signature. Classified as either type I or type II in roughly equal proportions, pRCC occurs either sporadically or as an inherited form [7]. In general, type I cancers are often multifocal and confer a better prognosis than the more aggressive and typically unifocal type II cancers [55].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations